The Adversity Quotient Of Middle Adult Women In Memorizing The Quran At The House Of Tahfidz Ummul Qura Banjarmasin, Indonesia - Mulyani; Faridah, Siti (Faculty of Ushuluddin and Humanities, 2023)
This study aims to look at the perseverance and ability of middle adult women aged 40-60 years in overcoming difficulties, challenges and obstacles in achieving success in memorizing al-Qur’an, without easily giving up. This is called adversity quotient. The subjects in this study were six people. This study aims to determine the type of adversity quotient of memorizing al-Qur’an, the factors that influence it and how to improve it. This study uses a qualitative descriptive phenomenology approach, with data collection methods of interviews, non-participant observation and documents. The results showed ER and NH is a type of climbers or runners or winners. Both of them are patient, optimistic, unyielding and big-spirited. Memorize according to the provisions and independently. Discipline in doing repeatation in reading 10-20 times until memorized. The ER subject had memorized 16 juz and NH has 5 juz of memorization. The other four people are walkers or campers. The four subjects are RD, MS and RS have memorized 2 juz of memorization, and SH has memorized 1 juz. The supporting factors for adversity quotient are high motivation, competitiveness, productivity, the ability to take risks, make improvements, persistence and willingness to learn. To increase adversity quotient is by listening to responses to the difficulties faced, tracing the causes of problems, analyzing evidence of the causes of difficulties and doing because they already have adversity quotient. Keywords: Adversity quotient, middle adult women, memorizing al-Qur’an.